Appropriate adult - Jones, Dan 1950- (ITV Studios, 2011)
Appropriate Adult tells the extraordinary story of Gloucester housewife Janet Leach who played a key role in the uncovering of the crimes of Fred and Rosemary West. This factual drama centres on the period of time between Fred West's arrest, his suicide in 1995 and the conviction of Rosemary West, and how Fred confided in Janet Leach who took the role of the 'appropriate adult' during his police interviews. 'Appropriate adults' are volunteers who can be asked by the police to sit in on interviews with minors or vulnerable adults in order to assist them and safeguard their rights
Original: Großbritannien 2011
Bildformat 16:9
Keywords: Film; DVD-Video